2022
DOI: 10.1126/scisignal.abm6046
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of TrkA mutations in patients with congenital insensitivity to pain reveals PLCγ as an analgesic drug target

Abstract: Chronic pain is a major health issue, and the search for new analgesics has become increasingly important because of the addictive properties and unwanted side effects of opioids. To explore potentially new drug targets, we investigated mutations in the NTRK1 gene found in individuals with congenital insensitivity to pain with anhidrosis (CIPA). NTRK1 encodes tropomyosin receptor kinase A (TrkA), the receptor for nerve growth factor (NGF) and that contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…The neighbor mutations L694P and G571R cause a similar R649W phenotype leading to pain and temperature insensitivity, anhidrosis and speech delay in patients pointing out the robust link between TKD TrkAmutations and HSAN IV disease ( 36 , 39 , 40 ). Indeed, structural mapping of HSAN IV TrkA variants has recently indicated that mutations located in TKD can affect the TrkA interaction with substrates, such as PLCγ, and these damages in TrkA-PLCγ interactions may have an analgesic effect on pain states in mice ( 41 ), given that the recruitment of PLCγ to TrkA is essential for NGF-mediated sensitization ( 42 ). In addition to mutations in the TKD mutations, other HSAN IV TrkA mutations are located in the extracellular domain, such as L213P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neighbor mutations L694P and G571R cause a similar R649W phenotype leading to pain and temperature insensitivity, anhidrosis and speech delay in patients pointing out the robust link between TKD TrkAmutations and HSAN IV disease ( 36 , 39 , 40 ). Indeed, structural mapping of HSAN IV TrkA variants has recently indicated that mutations located in TKD can affect the TrkA interaction with substrates, such as PLCγ, and these damages in TrkA-PLCγ interactions may have an analgesic effect on pain states in mice ( 41 ), given that the recruitment of PLCγ to TrkA is essential for NGF-mediated sensitization ( 42 ). In addition to mutations in the TKD mutations, other HSAN IV TrkA mutations are located in the extracellular domain, such as L213P.…”
Section: Resultsmentioning
confidence: 99%
“…Our in vitro data indicate that the altered molecular characteristic and trafficking of TrkA R649W protein could be the underlying mechanism affecting pain sensitivity in HSAN IV patients. Recently, structural mapping of HSAN IV TrkA variants indicates that mutations located in TKD can affect the TrkA interaction with substrates, such as PLCγ, and damages in TrkA-PLCγ interactions may have an analgesic effect on pain states in mice ( 41 ). In this regard, we recently generated PC12 cell lines lacking one or both NGF receptors using CRISPR/Cas9 ( 13 ), which provide a genetically clean background for the expression of TrkA R649W to study the specific signaling features.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is difficult to employ anti-NGF treatment for pain suppression as NGF produces many beneficial effects, in particular, via TrkA receptor activity. However, the latter limitation could be overcome by uncoupling TrkA from PLCγ signalling without inhibiting the TrkA catalytic activity [99]. This approach should avoid the unwanted effects of direct TrkA inhibition and probably can be used for anti-nociceptive applications in migraine and other pain conditions.…”
Section: P2x3 Receptors and Neuronal Sensitization In Migrainementioning
confidence: 99%